An effective approach for water pollution remediation and structural-optical analysis of gamma-irradiated flufenamic acid - N.C. Prachalith; Bibi Raza Khanam; Basavaraj Angadi; H.M. Suresh Kumar; Pravin Kumar; Birendra Singh; U.V. Khadke (Next Materials)
The escalating presence of pharmaceutical pollutants in aquatic ecosystems poses a significant environmental challenge, necessitating the exploration of innovative remediation strategies. Flufenamic acid, a non-steroidal anti-inflammatory (NSAID) drug and widely used analgesic, is recognized as an emerging contaminant due to its incomplete removal in conventional wastewater treatment processes. This research investigates the impact of high-energy gamma irradiation on the structural and optical properties of flufenamic acid to evaluate its potential for water purification and the development of novel chemo-sensors. Flufenamic acid samples were subjected to varying doses of gamma irradiation (0, 25, 50, and 75 kGy) from a 60Co source, and the resulting structural and optical modifications were characterized using XRD, Raman spectroscopy, Fourier-transform infrared spectroscopy, UV-Vis spectroscopy, and fluorescence spectroscopy. XRD analysis confirmed irradiation-induced structural modifications, including a transformation from Form I to Form II, in addition to the changes in lattice parameters, crystallite size, dislocation density, and lattice strain. These modifications were further validated by FTIR spectroscopy and Raman scattering, revealing significant alterations in FLA’s optical properties, as evidenced by UV-absorption, fluorescence, Raman, and FTIR spectroscopy. Notably, the 25 kGy. Irradiated sample exhibited enhanced Urbach energy, indicating increased disorder and chain scissoring, while its lowest absorbance suggested material degradation. Despite these structural changes, the optical energy band gap, derived from Tauc plots, remained unchanged within error bars across all doses. Moreover, a new fluorescence peak at ∼518 nm appeared, attributed to oxygen-related defects. These dose-dependent modifications in FLA’s structure and photoluminescence properties highlight its potential for water purification and the development of a new class of chemo-sensors.